Comparison of the efficacy of desmopressin fast-melting formulation and enuretic alarm in the treatment of monosymptomatic nocturnal enuresis. Issue 5 (October 2020) - Keten, Tanju; Aslan, Yilmaz; Balci, Melih; Erkan, Anil; Senel, Cagdas; Oguz, Ural; Kayali, Mustafa; Guzel, Ozer; Karabulut, Erdem; Tuncel, Altug
Summary: Background: Primary monosymptomatic nocturnal enuresis (MNE) is a common pediatric condition and there are two firstline, evidence-based treatments available; desmopressin and the enuresis alarm. Although there are many studies comparing enuresis alarm and desmopressin treatments in the literature, most were conducted using old formulations of desmopressin. Objective: To compare the efficacy of desmopressin MELT formulation and enuresis alarm therapy in patients with MNE. Study design: A total of 130 patients who had primary MNE were included in the study. The patients were divided into two groups using simple randomization; desmopressin MELT (Group 1, n = 66) and enuresis alarm (Group 2, n = 64). The patients were invited for a follow-up visit at the fourth, 12th and 24th weeks of treatment. Treatment response and compliance were evaluated using bed-wetting diary and ICSS criteria. Results: The mean age of the patients Group 1 and 2 was 11.2 + 3.3 and 10.2 + 3.4 years, respectively (p = 0.104). Complete response rate was similar at 4th week (53% vs. 37.3%, p = 0.162) and at 12th week (68.4% vs. 68.2%, p = 0.257). The relapse rate was significantly higher in the desmopressin MELT group than in the enuresis alarm group (48.9% vs 20.5%, p = 0.007). At the end of the study ten patients were excluded from the study because of loss to follow-up and/or side effects. The overall complete response rate was significantly higher in the enuresis alarm group than in the desmopressin MELT group at the end of the study (41.3% vs 64.9%, p = 0.035). When the intention to treat analysis population was considered, similarly the complete response rate was significantly higher in the enuresis alarm group than in the desmopressin MELT group (40.9% vs 64.1%, p = 0.027). Discussion: With regard to the management of children with MNE, our study revealed that desmopressin MELT and enuresis alarm both have high efficacy rates in primary MNE treatment both at 4th and 12th week. However, overall complete response rate was better in enuresis alarm treatment at 24th week. In addition, enuresis alarm treatment also presents as a more favorable relapse rate. Conclusions: Enuresis alarm presented a more permanent treatment response and a lower relapse rate than desmopressin MELT formulation. Summary Figure Image 2